Characterization of the Role of Amylo-Alpha-1,6-Glucosidase Protein in the Infectivity of Toxoplasma gondii - Cao, Xue-Zhen; Wang, Jin-Lei; Elsheikha, Hany M.; Li, Ting-Ting; Sun, Li-Xiu; Liang, Qin-Li; Zhang, Zhi-Wei; Lin, Rui-Qing (Frontiers in Cellular and Infection Microbiology, 2019)
In this study, we characterized the role of amylo-alpha-1,6-glucosidase (Aa16GL) in the biology and infectivity of Toxoplasma gondii, using Aa16GL-deficient parasites of type I RH and type II Prugniaud (Pru) strains. The subcellular localization of Aa16GL protein was characterized by tagging a 3 × HA to the 3′ end of the Aa16GL gene endogenous locus. Immunostaining of the expressed Aa16GL protein revealed that it is located in several small cytoplasmic puncta. Functional characterization of ΔAa16GL mutants using plaque assay, egress assay and intracellular replication assay showed that parasites lacking Aa16GL exhibit a slight reduction in the growth rate, but remained virulent to mice. Although PruΔAa16GL tachyzoites retained the ability to differentiate into bradyzoites in vitro, they exhibited slight reduction in their ability to form cysts in mice. These findings reveal new properties of Aa16GL and suggest that while it does not have a substantial role in mediating T. gondii infectivity, this protein can influence the formation of parasite cysts in mice.